Attempted ring contraction of α-triflates of 3-azido- and 3-fluoro-γ-lactones to oxetanes - Elliott, R; Fleet, G; Vogt, K; Wilson, F; Wang, Y; Witty, DR; Storer, R; Myers, P; Wallis, C (1990)
α-Triflates of 3-azido- and 3-fluoro-γ-lactones with potassium carbonate in methanol give mainly contrasting elimination products, rather than oxetanes; a methyl 3-azido-oxetane-2-carboxylate was isolated in low yield. © 1990.